The role of serpin protein on the natural immune defense against pathogen infection in Lampetra japonica. Issue 92 (September 2019) - Wang, Dayu; Gou, Meng; Hou, Jianqiang; Pang, Yue; Li, Qingwei
Abstract: Serine protease inhibitors (serpins) are a large protein family that is involved in various physiological processes and is known to regulate innate immunity pathways. However, research for the functional study of serpins in lamprey is limited. In the present study, a serpin gene was cloned and characterized from Lampetra japonica at molecular, protein and cellular levels, named L-serpin which belongs to family F serine protease inhibitors (serpin family). The L-serpin includes a serpin domain in the N-terminus. The mRNA transcript of L-serpin was extensively expressed in kidney, supraneural body, intestine, liver, heart, gill and the highest expression in leukocytes. The mRNA expression level of L-serpin increased significantly after Vibrio anguillarum, Staphylocccus aureus and Poly I:C stimulation and dramatically peak at 8 h. It is demonstrated that the L-serpin protected cells from lethal Gram-negative endotoxemia through associating with inhibition of lipopolysaccharide (LPS)-triggered cell death and inflammatory factors expression. Surface plasmon resonance (SPR) and the microbe binding assay were used to determine that L-serpin interacts directly with LPS (KD = 6.14 × 10 −7  M). Furthermore, we confirmed L-serpin is a major inhibitor of complement activation by inactivating lamprey-C1q protein (KD = 2.06 × 10 −6  M). Taken together, these findings suggest that L-serpin is a endogenous anti-inflammatory factor to defend against Gram-negative bacterial challenge and involved in lamprey innate immunity. Highlights: A serpin gene named L-serpin belongs to clade F and group V4 serpin family was cloned and characterized from lamprey . Bacterial multi-stimulation induces L-serpin expression in leukocytes and serum. L-serpin protects cells against LPS-mediated cell death and displays LPS binding activities. L-serpin inhibits the complement-dependent cytotoxicity of lamprey serum via binding to L-C1qDC-1.